The Plasticity of Thought in Translation - Shread, Carolyn (TTR, 2024)
My first translation of French philosopher Catherine Malabou’s work is “An Eye at the Edge of Discourse” (2007), in which she asks “What is it to see a thought? To see a thought coming?” This question prompted me to ask in turn, “What is it to see a thought coming in translation?” I put this question to readers of translations and, in a self-reflexive move, as a translator of her French thought into English. Engaging a seminar on this topic in which Malabou offered a retrospective account of how plasticity has emerged in her work over more than two decades, I consider its transdisciplinary potential specifically as it manifests in the field of translation, and here in the translation of scholarly thought.Following this retrospective gaze, I consider a recent article that is still untranslated from the French, Malabou’s “Quand on n’a que le discours: Réflexions sur la forme” (2022a). Drawing on the intersection of thinking and seeing, I refer to three artists—Kader Attia, Sophia Wallace, and Pearl Shread—to explore the valences of visibility and intelligibility, as well as routes of access to thought and knowledge.I conclude my discussion with brief reflections on my recent Malabou translation Stop Thief! Anarchism and Philosophy (2023), suggesting that the act of translation offers a possible route to autonomy and self-determination in the face of dominating effects of governance.